2009
DOI: 10.1016/j.chom.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of Macrophage Phagocytic and Antimicrobial Programs in Leprosy

Abstract: SUMMARY Effective innate immunity against many microbial pathogens requires macrophage programs that upregulate phagocytosis and direct antimicrobial pathways, two functions generally assumed to be coordinately regulated. Here the regulation of these key functions was investigated in human blood-derived macrophages. IL-10 induced the phagocytic pathway, including CD209 and scavenger receptors, resulting in phagocytosis of mycobacteria and oxLDL. IL-15 induced the vitamin D-dependent antimicrobial pathway and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
187
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(212 citation statements)
references
References 53 publications
(78 reference statements)
16
187
0
6
Order By: Relevance
“…Networks of genes involved in "endocytosis," "lysosome," and "phagosome" were identified and associated with macrophages, possibly reflecting the presence of IL-10-derived CD163 + M2 macrophages, which are programmed to be highly phagocytic (16,25). A lipid-binding pathway was present in L-lep lesions, which is consistent with the observation that host-derived lipids accumulate in macrophages in L-lep lesions (63).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Networks of genes involved in "endocytosis," "lysosome," and "phagosome" were identified and associated with macrophages, possibly reflecting the presence of IL-10-derived CD163 + M2 macrophages, which are programmed to be highly phagocytic (16,25). A lipid-binding pathway was present in L-lep lesions, which is consistent with the observation that host-derived lipids accumulate in macrophages in L-lep lesions (63).…”
Section: Discussionsupporting
confidence: 74%
“…As part of this network, other genes involved in "chemotaxis" and "tissue remodeling" included IRF6, ADIPOQ, OVOL1, and FOXQ1 (43)(44)(45)(46)(47)(48). Another prominent gene, CYP27B1, a member of the cytochrome p450 family, is a critical part of the vitamin D antimicrobial pathway to kill mycobacteria (16,25,49,50). Together, these networks link chemotaxis, tissue remodeling, and antimicrobial activity as part of the effective host response to limit mycobacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Sulahian and colleagues [12,27] have demonstrated that IL-10 directly elevates CD163 mRNA. Since previous work has described the role of IL-10 in LL pathogenesis [10], we suggest that this cytokine is responsible for the maintenance of the heightened levels of CD163 in LL cells. It has also been shown that the IL-10 induction of scavenger and opsoninic receptors may facilitate antigen loading and initiate antigen presentation and adaptive immune responses to the infectious agent [28].…”
Section: Discussionmentioning
confidence: 99%
“…Foamy macrophages seem to sustain intracellular mycobacteria in a physiological state similar to a nonreplicating vegetative one [9]. In this context, Montoya et al [10] demonstrated that lepromatous macrophages exhibit a high expression of the cysteine-rich superfamily scavenger receptor (SRCR), which increases the phagocytic capacity of macrophages and leads to a reduction in bactericidal activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, M2 polarization is also associated with reduced host defense and chronic infection. For example, high levels of IL-10 and enrichment of other M2-associated gene expression profiles are found in lepromatous lesions in comparison to the tuberculoid lesions of Mycobacterium leprae infection (32). Chronic infection by several bacteria, such as Tropheryma whipplei, is associated with enhanced M2c polarization and suppressed M1 activation (12,33).…”
mentioning
confidence: 99%